TAFSIR MISOGINIS AYAT-AYAT IDDAH: Analisis Sosiologis Ayat-Ayat Iddah Menurut Mufassir dan Ahli Fiqh - Muttakin, Khairul (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2017)
One issue that arises today is about the waiting period for women, either died or idda divorce waiting period. Because the prescribed period (of waiting) for women in a relatively long period of time. If that be the reason for the length of the prescribed period, one of which, is to determine about the possibility of the women were pregnant or notÂ then with modern technology can already be known to women pregnant or not without having to wait for several months. This is the theme of the discussion in this article because the waiting period (iddah) for women under the spotlight from opponents who take the position of Islamic law (the issue of the prescribed period for women) tend to be unreasonable. In addition glare comes from the feminist questioning the prescribed period like women only, while the male is no such thing prescribed period and may not directly get married after the divorce. This will bring up the notion that the verses of the Koran that talk about issues iddah tend misogynistic and view women are lower than men's. By combining the approach of islamic law and the interpreter opinion of classical and modern would be associated with the formulation of Islamic law more reasonable and acceptable, especially for opponent.Â